Design e avaliação de uma aplicação mobile para surf em grupo - João Filipe Paiva de Amicis Rebelo (2018)
Surf is a sport that has been growing exponentially. Nowadays, there are many aplications in our society that help surfers with very useful tools, however, we can still observe that there are many gasps to deal with. In the present days it is possible to notice the lack of support of the community for those that are still taking the first steps in the sport. Even those that have some experience in surfing, need a group to continue their evolution. It is crucial to work on surf in group aplications that enable: the shareness of contentes, give and observe surf reports in first person, schedule surf sessions in group and do other things. In this dissertation its proposed to develop a prototype of an application that responds to that kind of needs. The objective is to develop the prototype and further evaluate it with usability tests. The essential problem of the study is to identify the key features for the main target of the application, design, prototype and evaluate ways of applying those features, to achieve a solution. It also important to test the features with the potential users. Regarding the literature review, several topics important for the study are discussed. In the topic of usability evaluation, several concepts of different authors are addressed. Authors like Nielsen, Cooper, Lowdermilk, Rubin, and others are discussed in the work. Concerning the surf applications, in this literature review, are made 3 important case studies for the development of the prototype. In this study a qualitative approach was adopted through the usability evaluation of the application mockup. The participants are the surfers of the north, a parcel of the potential users that eventually could use the application. The research design used was the type 1 investigation of involvement and the instruments used are: initial questionaires, gathering of requirements and features, preparation and moderation of the teste, questionnaire of background, test, final interview and questionnaire. The results show us that the concept and design of the app is very captivating, as well as the features applied to the prototype. Despite of these positive facts, some errors of usability were detected during the tests. During the study there were some limitations and constraints. The product is only a prototype and there are still some items to uncover and explore with the users. The challenge in future works is to test again the application with the corrections based on the feedback of the usability tests and continue this way the iterative cycle of the product. It would be interesting to launch the aplication in the market and observe how users react and if the product matchs the users expectations. Como trabalho futuro, é pertinente testar novamente a aplicação com as melhorias sugeridas nos testes de usabilidade e implementa-la. Depois de lançar o produto seria interessante investigar durante uns meses se a aplicação corresponde mesmo às expecativas dos utilizadores.